Increasing the Effectiveness of the Learning Exchange Model: The Role of MSME Facilitators in the CIKEPO MSME Community - Emi, Chiara; Rahmat Pramudia, Joni; Sukmana, Cucu; Sardin, Sardin (Universitas Negeri Padang, 2024)
MSME facilitators are crucial in supporting the region's development of Micro, Small, and Medium Enterprises. MSME companions represent the 17th SDGS goal, namely partnerships to achieve goals (partnerships for the goals). This research aims to determine the effectiveness of learning exchange: The role of UMKM Facilitator in the CIKEPO Community of Cimahi City. This research uses a descriptive method with a qualitative approach—data collection techniques using interviews and documentation. MSME Facilitators have a role in encouraging awareness of MSME players in following the learning exchange process, which can improve skills. Also, MSME Facilitators provide education and training for MSME owners, including business management, marketing, and understanding local business regulations. Apart from that, MSME mentors also provide individual business guidance to help MSME owners identify potential and overcome the challenges they face.Keywords: MSME Companion, Learning Exchange